"Polarity, Paradox and the Organizing Process in Development"; Parent-Infant Psychotherapy and Child Analytic Technique: In Honor of Louis Sander. Issue 1 (2nd January 2019) - Herzog, James M.
ABSTRACT: A child analysis and a subsequent family therapy are presented and discussed in terms of Sander's monumental contributions to infant-parent development and clinical theory. I draw on earlier discussions with Sander on these topics and note how his insights validate a certain kind of child analytic technique I practice.